Assessment on problems of issuances and transferences of Strata title in Malaysia: The perception of the owner - Kamaruzzaman, S.N.; Muhamad Salleh, N.; AlZawawi, S.A.F. (2010)
The ownerships of property as an asset, is a long-term investment for the owner. Strata Titles is a document of title which endorsed by the land administrator for the whole parcels of a subdivided multi storey building. Strata Titles important to purchasers as a proof of the ownership of the parcels they purchased as they will able to persevere any deal which stated in Part IV of National Land Code that aloud any titles’ transferred, mortgage, leasing and any permitted activities to be carried out. However, there are problems in applying strata tittles which will affect the ownerships of the parcels in a multi storey building. Normally, everyone will blame the developers as the causes of failure to appraise the issuance of the Strata Titles. This study will be focused on the problems which caused the failure of the issuances and the transferred of the strata to the purchasers. The study analyse from the perceptions of the owner of the parcels. The findings of the survey found that the service and the maintenance fee are slightly high compared to the services offered by the Management Corporations. Besides, the owner refused to pay any outstanding bills on maintenance of their building and the mortgage and stamp duty disbursements are another factor for them to refuse the transference of ST. Based on these findings, several recommendations identified to reduce the problems of the issuance and transfer of the Strata Titles to the purchasers by providing transparent information, campaign